Evaluation of the Sensitivity and Specificity of Circulating MicroRNAs to Diagnose Breast Cancer: A Systematic Review and Meta-analysis - Pallavi Prakash; Jason Widjaja; Cicilia Marcella; Baiyun Sun (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: Today, scientists use cell-free circulating microRNAs (miRNAs) biomarkers to identify, control, and treat cancer, even in its early stages. The present study aimed to evaluate the sensitivity and specificity of circulating microRNAs to diagnose breast cancer.Material and methods: The search was conducted based on keywords related to the study objectives in the international databases PubMed, Scopus, Science Direct, ISI, Web of Knowledge, and Embase between January 2015 and March 2023. Effect size (95% confidence interval) was calculated using the fixed effect model with the inverse-variance method. STATA/MP. V17 software was used for meta-analysis.Results: In the present study, 31 articles were included in the meta-analysis. Sensitivity of circulating microRNAs to diagnose breast cancer was 85% (ES: 0.85 [95% CI: 0.74, 0.95]. Specificity of circulating microRNAs to diagnose breast cancer was 85% (ES: 0.85 [95% CI: 0.75, 0.96]. The AUC of miR-21 to diagnose breast cancer was 84% (ES: 0.84 [95% CI: 0.71, 0.97].Conclusions: Based on the present meta-analysis, circulating microRNAs are promising biomarkers in breast cancer diagnosis.